OPTIMASI DAN VALIDASI METODE PENETAPAN KADAR KURKUMIN DALAM PLASMA MANUSIA (IN-VITRO) SECARA KROMATOGRAFI CAIR KINERJA TINGGI - , C.E. Dhurhania; , Prof. Dr. Sudibyo Martono, M.S., Apt. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Curcumin is the major yellow pigment of curcuma. Recently, it has been reported that curcumin exhibit numerous pharmacological activities, thus makes interesting to study curcumin in preclinical and clinical research. Therefore, it is necessary to validate bioanalytical method associated with the use of curcumin in clinical laboratories. This study was done in order to obtain optimum conditions and the High Performance Liquid Chromatography (HPLC) method validity, with a C18 column and UV-vis detector, using the SPE HLB, in the determination of curcumin in human plasma. In this study has been used Shim-pack (Shimadzu) VP-ODS column (150 x 4,6 mm